Ambiente de ensino e aprendizagem de computação aplicando a técnica OC2-RD2 com desafios CTF - Freitas, Marcio Alexandre de (2021)
This study was conceived with the objective of investigating which uses the challenges of capturing the flag or CTF, from the English "Capture the Flag" in the teaching of computing. Initially the CTF was designed for competitions between cybersecurity specialists, but teachers identified pedagogical benefits that can be used for teaching computing. Despite the fact that CTF competitions require great efforts from people and computational resources that are not common to be available in computer courses, teachers started to look for alternatives to adapt CTF challenges to teaching and learning environments. Leaning on the OC2-RD2 teaching and learning technique, specific to computer teaching, this work proposes a computing class with exercises based on CTF challenges. The increase in cyber attacks, especially after organizations have granted remote access to their employees on behalf of COVID-19, has increased the need for this research. Research shows that most of these attacks are due to human failure in the construction of systems, mainly due to the low qualification of professional developers and network administrators in cyber security. The surveys also point out the lack of professionals specialized in cybersecurity to work together with other ICT professionals. The bibliographic review of this study points the way to the insertion of cyber security in the computing disciplines with promising results from the use of CTF in universities in raising the level of student engagement with a consequent decline in dropout and an increase in the use of students in evaluations